Entre o Centro Histórico, a Praia Grande e o “Projeto Reviver”: espaços de socialização LGBTQIAPN+ em São Luís - MA - Costa, Angela de Cassia (2023)
This research aims to understand the processes of LGBTQIAPN+ socialization in the Historic Center of São Luís – MA. It has a quantitative and qualitative character. A vast bibliographical review, field research was carried out using questionnaires, interviews and photographic surveys to create a map that shows the location of leisure establishments and socialization areas in the Historic Center of São Luís – MA. A profile questionnaire was also used with the aim of better understanding the profile of LGBTQIAPN+ people who frequent socializing and leisure spots, as well as hearing their opinions about the area studied. The theoretical contribution of this research relied mainly on the studies of Foucault (1979, 1988, 2010, 2022), Facchini (2005), Quinalha (2020 and 2022), Louro (2009) for working on the topic of homosexuality on a large scale. The results showed that the Historic Center of São Luís is an area of leisure and socialization establishments for all audiences, however, from the beginning of the 1990s, the countless squares, nightclubs, bars and nightclubs that make up it have become a space of cultural effervescence, of struggles for rights, of leisure and socialization with greater security for LGBTQIAPN+ people, moreover, the object of study of this Dissertation is linked to the Zona do Baixo Meretriz – ZBM – of São Luís in end of the 1970s.